Influence of psychological autonomy support of peer instruction: A novel interactive approach using Instagram in language learning - Alfadda, Hind; Afzaal, Muhammad; Mahdi, Hassan; Alaudan, Rasha; Curle, Samantha (Frontiers in Psychology, 2022)
This study makes an original contribution to knowledge by investigating the impact of Just-in-Time (JiT) teaching and peer instruction (PI) strategies on the promotion of students’ achievement, interaction, and motivation in English language learning. Students were recruited from an undergraduate TESOL program in the first semester of 2019 at a University in Saudi Arabia. A multiple method research design was used to address the research questions robustly and rigorously. First, a two-group quasi-experimental design was implemented. In the first group, a lecture-based strategy was used (n = 28), while in the second group, JiT and PI strategies were used (n = 27) in English language lessons. An innovative research method was used in this study: a private Instagram account was created, serving as a platform through which teacher and students could communicate using interactive posts and comments. Second, students filled out a survey reflecting on this medium of language teaching and learning. Finally, focus group interviews were conducted to determine students’ views on the use of Instagram as an educational tool in terms of its flexibility and usefulness. The findings of the study suggest that JiT teaching, and PI promoted students’ achievement and enhanced students’ motivation, particularly in relation to fluency and novelty in the second language. Furthermore, students viewed Instagram as a successful educational tool that significantly facilitated their collaboration. Nevertheless, this study also highlights the challenges of using JiT teaching and PI to facilitate language learning. Suggestions for practitioners are specified; including providing adequate e-learning tools for students to enhance language learning motivation and achievement.